An experimental study on the offset-strip fin geometry optimization of a plate-fin heat exchanger based on the heat current model. (25th May 2019) - Hao, Jun-Hong; Chen, Qun; Ren, Jian-Xun; Zhang, Meng-Qi; Ai, Jing
Highlights: Propose a new heat current method-based solution for heat exchanger design and analysis. Optimize the fin structures of a compact heat exchanger by the tree traversal method. Construct an experimental setup to test the thermal-hydraulic performance for validation. Obtain the heat transfer coefficient and flow resistance of the improved heat exchanger. Provide an empirical correlation for fin structure optimization in practical application. Abstract: The compact heat exchanger is significant for hybrid and electric/fuel cell vehicles with high energy utilization efficiency. This contribution introduces the heat current method to propose a new solution for the design and optimization of heat exchanger structure by combining the empirical correlations of heat transfer and flow resistance. On the premise of decreasing the air flow length of a plate-fin heat exchanger, the tree traversal method is utilized to optimize the offset strip fins on both the hot and the cold fluid sides of a plate-fin cross-flow heat exchanger. Moreover, an experimental setup is built for testing the thermal-hydraulic performances of the original and improved heat exchangers. The results show that the difference between the experimental and the theoretical results is less than 3.23% which represents the heat current method is feasible for heat exchanger analysis and optimization. Meanwhile, the total heat transfer coefficient increases by 7.43% and the pressure loss on the air side reduces by 29.7% for the improved heat exchanger, which is more suitable and high-efficient for the limited space in a high-power vehicle. Finally, the corresponding functions of the total heat transfer coefficient and pressure loss with different air mass flow rates are constructed for future practical applications of the improved heat exchanger.